IP3R3 gene expression in laying duck tissues and its polymorphisms associated with eggshell quality - Zhao, Yong; Li, Jiezhang; Ma, Jinshuai; Ding, Yijie; Fu, Hongmei; Zhang, Yiyu (Gene, 2025)
•IP3R3 showed highest expression in the eggshell gland among 11 duck tissues.•SNP g.16132 C > T was linked to eggshell thickness, CC and CT outperformed TT.•Certain diplotypes significantly enhanced eggshell strength and shape index.•IP3R3 is a candidate gene for improving eggshell quality via genetic selection. Inositol triphosphate receptor type III (IP3R3) is a key second messenger that mediates the release of intracellular Calcium ion (Ca2+). It binds to inositol triphosphate (IP3) to form a calcium channel, regulating intracellular calcium homeostasis. This study aimed to analyze IP3R3 mRNA expression in duck tissues and its single nucleotide polymorphism (SNP) association with eggshell quality. Forty-five-week-old Guizhou Sansui ducks were used as experimental subjects. The real-time fluorescence quantitative PCR (qRT-PCR) assessed gene expression, while SNPs were identified via PCR products sequencing. The association between SNPs, diplotypes, and eggshell quality was analyzed using SPSS 18.0. Four SNPs were identified in the IP3R3 gene: g.16132 C > T (exon 8), g.35267 T > C (exon 50), g.35279 G > A (exon 50), and g.35497 C > A (exon 51). All four SNPs were synonymous mutations that did not alter the encoded amino acids. The SNP g.16132 C > T polymorphism significantly affected eggshell thickness (P < 0.05). Diplotypes H1H1 and H2H2 were significantly greater than the eggshell thickness of H1H2 and H5H5 individuals (P < 0.05). Diplotypes H1H2 and H5H5 significantly increased eggshell strength, while H1H5 significantly improved the egg shape index. Additionally, H1H3 significantly enhanced egg weight and eggshell weight. The IP3R3 mRNA was expressed at varying levels across 11 tissues in Sansui ducks, with the highest expression in the eggshell gland, followed by the heart, spleen, glandular stomach, pancreas, kidney, liver, small intestine, lung, breast muscle, and masticatory stomach. The IP3R3 gene can serve as an important candidate gene, with potential application as a molecular marker in poultry breeding programs, including marker-assisted selection (MAS) and genomic selection, to improve eggshell quality in laying ducks.